The use of rockfish Sebastiscus marmoratus as a sentinel species to assess petroleum hydrocarbons pollution: A case study in Quanzhou Bay, China. Issue 2 (30th November 2017) - Bo, Jun; Zheng, Ronghui; Kuang, Weiming; Hong, Fukun; Xie, Qing; Zhang, Yusheng
Abstract: To monitor the biological effects of marine pollution, choosing a native fish species and establishing suitable biomarkers are required. In this study, the full-length cDNA of cyp1a1 was cloned from Sebastiscus marmoratus (SM-CYP1A1). Then the dose-response and time-course induction of hepatic CYP1A1 mRNA by the crude oil water-soluble fraction (WSF) were determined. Subsequently, SM-CYP1A1 mRNA was applied to investigate the biological effect of petroleum hydrocarbon pollution in Quanzhou Bay, China. The transcription levels of hepatic CYP1A1 were significantly elevated in fish caged in the polluted sites for 2 weeks compared with those of the reference site, which were correlated with the concentrations of petroleum hydrocarbon and polycyclic aromatic hydrocarbon (PAH) in the surface seawaters. The results suggest that S. marmoratus is a potential sentinel organism to monitor marine pollutants and the hepatic CYP1A1 mRNA can serve as a sensitive biomarker to organic xenobiotics in aquatic environments. Highlights: A full-length cDNA sequence of cyp1a1 was determined from Sebastiscus marmoratus . Expression of SM-CYP1A1 mRNA was correlated with the content of petroleum. SM-CYP1A1 mRNA can serve as a sensitive biomarker to petroleum hydrocarbons pollution. S. marmoratus is a potential sentinel species to monitor marine pollutants.